Histopathologie der Pannikulitis: Aspekte der Biopsietechnik und Schwierigkeiten der Diagnostik = Histopathology of panniculitis : aspects of biopsy techniques and difficulties in diagnosis - Rose, Christian; Leverkus, Martin; Fleischer, Mariella; Shimanovich, Iakov (Journal der Deutschen Dermatologischen Gesellschaft, 2012)
BACKGROUND: Clinical and histologic diagnosis of panniculitis may be difficult. The patients usually present with erythematous subcutaneous nodules with or without additional symptoms. If a skin biopsy does not include enough subcutaneous fat, histopathologic assessment is limited and the correct diagnosis may be delayed and require further sampling. PATIENTS AND METHODS: To illustrate the difficulties in the diagnosis of panniculitis, we performed a retrospective examination of four patients with different forms of panniculitis. RESULTS: In two patients with subcutaneous panniculitis-like T cell lymphoma and lupus panniculitis, the correct diagnosis could only be ascertained after a delay of several months because repeated biopsies had to be obtained throughout the course of disease. In two further patients with cold panniculitis and pancreatic panniculitis, clinicians did not even suspect an inflammatory process in the subcutaneous tissue. The correct diagnosis was made with a deep punch biopsy that included subcutaneous fat. CONCLUSIONS: On the one hand, these examples demonstrate the importance of sampling subcutaneous tissue when obtaining routine punch biopsies. On the other hand, in cases where the diagnosis is uncertain, it is necessary to perform large and deep incisional biopsies.
Gesehen am 17.04.2018